Modified Gustafson’s Method for Age Estimation from Premolars: A Study Employing Dental Panoramic Tomographs - Donni Sonjaya; Phrabhakaran Nambiar; Haslinda Ramli; Aspalilah Alias (jidmr, 2024)
Indexed by Scopus